(Ne)omejenost tvorbe feminativov v slovenščini - Markežič, Tjaša (Slavia Centralis, 2020)
(Un)limited composition of feminine forms in SloveneWord formation analyses from the nineteen-eighties and nineties note that feminine equivalents cannot be created for all masculine designations of beings. Data from language corpora and the world wide web prove that the formation of the majority of those is not only possible but also quite common, while some of them are making their first steps towards colloquial use. The possible absence of some female parental parallels can be socio-historically and biologically conditioned.
Keywords: Slovene language; word formation; feminine equivalents; gender inequality